Концепции высокоточной механической обработки деталей машин - Новиков, Федор Васильевич; Полянский, Владимир Иванович; Дитиненко, Станислав Александрович; Крюк, Анатолий Григорьевич (НТУ "ХПИ", 2017)
Сформулированы основные условия повышения эффективности механической обработки высокоточных деталей машин на основе применения прогрессивных методов высокоскоростного резания на современных станках с ЧПУ типа “обрабатывающий центр” и высокопроизводительных сборных конструкций инструментов с износостойкими покрытиями. Показана эффективность применения разработанной физико-математической теории процессов обработки материалов и технологии машиностроения, позволяющей с единых позиций производить теоретический анализ и оптимизационные расчеты технологических параметров лезвийной и абразивной обработки. Приведено новое теоретическое решение об определении технологических возможностей уменьшения погрешностей обработки при растачивании отверстий, обусловленных упругими перемещениями, возникающими в технологической системе. Даны практические рекомендации.

The main conditions for increasing the efficiency of machining high-precision parts of machines based on the application of progressive high-speed cutting methods on modern CNC machines such as the "machining center" and high-performance prefabricated structures of tools with wear-resistant coatings are formulated. The efficiency of the application of the developed physical and mathematical theory of the processes of material processing and engineering technology is shown, which makes it possible to perform theoretical analysis and optimization calculations of technological parameters of blade and abrasive processing from single positions. A new theoretical decision is made to determine the technological possibilities of reducing processing errors during boring holes caused by elastic displacements arising in the technological system. It has been theoretically established that as the number of tool passes increases, the processing errors decrease quite intensively, according to the law of geometric progression. Therefore, from the point of view of increasing the accuracy of the hole size, it is advisable to remove the allowance in one or several passes of the tool, and from the point of view of increasing the alignment of the hole, on the contrary, it is necessary to increase the number of passes of the tool.
The concept of high-precision machining of machine parts
Keywords: машиностроение; точность; производительность; растачивание отверстия; перемещения упругие; система технологическая; engineering technology; machining; high-precision machine parts; processing capacity; machining accuracy; hole boring; elastic movements; technological system